HLA‐DQA1‐HLA‐DRB1 polymorphism is a major predictor of azathioprine‐induced pancreatitis in patients with inflammatory bowel disease - Wilson, A.; Jansen, L. E.; Rose, R. V.; Gregor, J. C.; Ponich, T.; Chande, N.; Khanna, R.; Yan, B.; Jairath, V.; Khanna, N.; Sey, M.; Beaton, M.; et al. (Alimentary pharmacology & therapeutics, 2018)
Summary Background Azathioprine (AZA)‐induced pancreatitis is an unpredictable and dose‐independent adverse event affecting 2%‐7% of patients with inflammatory bowel disease (IBD) patients treated with AZA. There are no tools in clinical practice to identify at‐risk individuals; however, a genome wide association study (GWAS) identified a strong association between the Class II HLA gene region polymorphism (rs2647087) and thiopurine‐induced pancreatitis. Aim To independently confirm the findings of the GWAS in an IBD cohort, to evaluate its utility in clinical practice and to offer a novel AZA treatment algorithm for IBD based on pharmacogenomic principles. Methods A retrospective cohort study evaluated 373 AZA‐exposed IBD patients from a tertiary care academic centre in London, Canada. Due to the limited number of patients taking mercaptopurine (MP), such patients were not included this cohort. All subjects underwent screening for the single nucleotide polymorphism (SNP) rs2647087 mapped to the HLA‐DQA1*02:01‐HLA‐DRB1*07:01 haplotype and were sub‐divided based on the presence (n = 13) or absence (n = 360) of an AZA‐induced pancreatitis diagnosis. The risk of AZA‐induced pancreatitis was assessed based on rs2647087 genotype. Results The risk of pancreatitis during AZA‐therapy was highly predictable and genotype dependent: 0.53% for wild type (A/A), 4.25% (OR = 4.19, 95% CI 1.02‐36.45, P = 0.044) for heterozygous (A/C), and 14.63% (OR = 15.83, 95% CI 3.80‐145.26, P = 0.0001) for homozygous variant (C/C) patients. Conclusions The class II HLA region (at rs2647087) is an important marker of AZA‐induced pancreatitis risk. We propose a simple and clinically implementable algorithm based on rs2647087 and TPMT genotypes for AZA selection and dosing for patients with IBD. Linked ContentThis article is linked to Teich et al and Wilson et al papers. To view these articles visit https://doi.org/10.1111/apt.14545 and https://doi.org/10.1111/apt.14562.